2022
DOI: 10.1111/1467-9477.12230
|View full text |Cite
|
Sign up to set email alerts
|

An emerging populist welfare paradigm? How populist radical right‐wing parties are reshaping the welfare state

Abstract: Populist radical right-wing parties (PRRPs) in Western Europe have almost without exception shifted their position on distributive issues, abandoning their earlier support for a minimal welfare state in favor of higher social spending. Recent studies suggest that PRRPs' distributive preferences go beyond the clash between simply expanding or retrenching welfare; instead, they defend a specific welfare state that focuses on consumption policies for the "deserving." Drawing on this literature and the welfare par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
1
9
0
1
Order By: Relevance
“…While initial analyses have found that the economic policies of RWPPs are anchored in right-wing economic discourse, recent assessments have found evidence that RWPPs frequently adopt economic policies which are characterized as being left-wing, such as more generous welfare transfers or higher taxes for wealthier citizens (Afonso and Rennwald, 2018). Ennser-Jedenastik (2018) and Chueri (2022) have instead argued that a more useful interpretative lens through which to understand the economic agenda of RWPPs is that of economic nativism, welfare chauvinism and deservingness.…”
Section: The Politics Of the Minimum Wagementioning
confidence: 99%
“…While initial analyses have found that the economic policies of RWPPs are anchored in right-wing economic discourse, recent assessments have found evidence that RWPPs frequently adopt economic policies which are characterized as being left-wing, such as more generous welfare transfers or higher taxes for wealthier citizens (Afonso and Rennwald, 2018). Ennser-Jedenastik (2018) and Chueri (2022) have instead argued that a more useful interpretative lens through which to understand the economic agenda of RWPPs is that of economic nativism, welfare chauvinism and deservingness.…”
Section: The Politics Of the Minimum Wagementioning
confidence: 99%
“…On the other hand, scholars argue that, despite their protective rhetoric, radical right politics are part of the self-regulating market movement, which supports disciplinary attitudes towards welfare, particularly targeting groups deemed as 'undeserving' (Chueri 2022), while, at the same time, prioritizing capital accumulation over protecting human well-being (Atzmüller and Décieux 2020;Lim 2021, p. 528;Scheiring and Szombati 2020). 2 While authors disagree on the importance of the role of economics in the agenda of populist parties, there is now a common understanding that contemporary populist radical right-wing parties have shifted their market-liberal stance.…”
Section: Disembedded Economy and Institutional Anomiementioning
confidence: 99%
“…2 While authors disagree on the importance of the role of economics in the agenda of populist parties, there is now a common understanding that contemporary populist radical right-wing parties have shifted their market-liberal stance. Instead of advocating for a minimal state, these parties now tend to support a strong but exclusionary welfare state (Chueri 2022) and embrace economic nationalism (Clift and Woll 2013), departing from global market liberalism (Betz 2003, p. 76;Mudde 2007). However, empirical evidence from countries such as Hungary (Scheiring and Szombati 2020), Austria (Ausserladscheider 2022), Turkey (Güven 2016), Britain (Hopkin 2017), and the US (Pierson 2017) suggests that when right-wing parties come to power, they tend to implement policies that benefit the wealthy and powerful rather than implementing policies that promote social and economic equality (Lim 2021).…”
Section: Disembedded Economy and Institutional Anomiementioning
confidence: 99%
“…Fidesz, in contrast, pursued exclusionary policies and sharpened the divide between 'insiders' in stable employment and lower-class 'outsiders'. Fidesz thus broadly followed the 'populist welfare paradigm' (Chueri, 2022) espoused by populist right-wing parties in Western Europe, with the refinment that its harsh policies related to the unemployed rather resemble 'exclusionary neoliberal populism' (Scheiring, 2021). In Turkey, government and opposition alike discursively endorsed the concept of the welfare state while Fidesz built up an alternative: the 'work-based society'.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%